Mitigating investor reactions to financial misconduct: the moderating roles of firm commitment cues - Ye, Lu (Journal of business ethics, 2025)
Corporate financial misconduct has garnered increased interest in business ethics research. Although prior research has provided insights into the consequences of financial misconduct, our understanding of why investors react differently to similar instances of misconduct, especially in emerging markets, remains limited. In this study, we first argue that direct information on the severity of misconduct is the primary basis for investors’ evaluations. Next, drawing on screening theory, we theorize that in contexts characterized by high information asymmetry, indirect information about existing firm commitment cues plays a vital screening role by demonstrating the firm's legitimacy and capability. Subsequently, we develop a tripod framework that integrates the social, market, and strategy dimensions as firm commitment cues that serve as fundamental screening mechanisms to mitigate the adverse effect of misconduct severity on investor reactions. We use a sample of 344 Chinese listed firms that engaged in financial misconduct during 2009-2019 and find that greater misconduct severity results in more negative investor reactions. However, this negative relationship is weakened when the firm demonstrates stronger social and strategy commitments but not stronger market commitment.